An analysis of North Korean trade amid warming global relations utilizing RCA, RSCA and TBI - Stephens, Aaron R; Kasamanli , Ramin (The European Journal of Applied Economics, 2020)
Based on high profile meetings with South Korean and US leaders, North Korean denuclearization and global economic cooperation is within sight. This paper seeks to outline trade policy opportunities for North Korea given such breakthroughs. This research summarizes international trade in North Korea and identifies sectors of the economy that are poised to further develop the North Korean economy. Employing three measures of trade specialization – RCA, RSCA, and TBI, this paper analyzes time series trade data from 2011 to 2018 in order to reveal specialized export sectors in North Korea. Chinese and UN bans on exports have been particularly damaging to exports from North Korea based on 2018 data. North Korea has comparative advantages in several sectors: coal, fisheries, and apparel among other areas. Trade in North Korea would lead to rapid industrialization and development if the country opens its economy; a well-managed approach would serve to direct development in specific sectors without sacrificing others; moreover, this research advises which sectors can be used to develop North Korea in an early stage of openness.